Does antibiotic resistance impair plasma susceptibility of multi-drug resistant clinical isolates of enterococci in vitro?. Issue 1 (December 2016) - Napp, Matthias; Podewils, Sebastian; Klare, Ingo; Haase, Hermann; Kasch, Richard; Gümbel, Denis; Ekkernkamp, Axel; Jünger, Michael; Daeschlein, Georg
Abstract Background Cold atmospheric plasma could constitute an alternative against multi-drug resistant pathogens. Susceptibility of enterococci to cold atmospheric plasma was investigated in vitro. Methods 39 clinical isolates of enterococci were grouped dependent on the most important resistance patterns and treated on agar using dielectric barrier discharge plasma. These included enterococci with combined vancomycin- and high-level gentamicin resistance, high-level resistance to gentamicin (HLGR) only, vancomycin resistance alone (VRE), and enterococci susceptible to both. Susceptibility to cold atmospheric plasma was evaluated based on the zones of inhibition and examined in terms of the enterococcal group and the "degree" of drug resistance. Results Cold atmospheric plasma treatment killed all groups. Comparison of VRE and HLGR strains with non-VRE and non-HLGR isolates concerning zones of inhibition revealed that enterococci with special resistance patterns (VRE and HLGR) showed significantly smaller zones of inhibition than the sensitive ones. The mean of all isolates, irrespective of belonging to groups, showed smaller zones of inhibition with increasing "degree" of drug resistance. Conclusions Cold atmospheric plasma treatment killed all isolates of enterococci, but its efficacy depended on the "degree" of drug resistance and on membership in special resistance groups with particular clinical-outbreak importance. However, a possible role of the different genetic lineages, which might be prone to acquiring more or less resistance phenotypes, may also play a role in this context.